A Study of Influence Tactics Used by Entrepreneurs - Singh, Lakshya; Yadav, Sresha; Dewangan, Shreyansh; Thakur, Vaibhav (AMC Indian Journal of Entrepreneurship, 2022)
Entrepreneurs have to deal with different stakeholders for the success of their ventures. These stakeholders include but are not limited to investors, employees, customers, and suppliers. An entrepreneur has to influence different stakeholders to support him during times of crisis or uncertainty. The present study analyzed different influence tactics used by the entrepreneurs with different stakeholders. The influence tactics taken into consideration include inspirational appeals, consultation, personal appeals, and exchange. Quantitative analysis helped conclude the tactic used with different stakeholders under different circumstances. The researchers hope this study will help entrepreneurs in selecting the right tactic and increase the chances of their ventureâ€™s success.Â Â